Trace copper determination in mate tea and tap water using FAAS and spray-assisted liquid phase microextraction - Karakebap, Kubra; Serbest, Hakan; Turak, Fatma; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
In the present study, a rapid, efficient and environmentally friendly analytical approach was proposed for the determination of trace copper by flame atomic absorption spectrometry (FAAS) after spray-assisted fine droplet formation based liquid phase microextraction (SFDF-LPME), which eliminates the use of dispersing solvents. With the help of a simple nozzle apparatus, an efficient distribution of the extraction solvent into the sample was achieved. The developed SFDF-LPME-FAAS method achieved a limit of detection (LOD) of 1.6 mu g L- 1 and a limit of quantification (LOQ) of 5.2 mu g L- 1 under optimal conditions. A wide linear range was recorded with a regression coefficient (R2) of 0.9987 between 5.0 and 100 mu g L- 1. The improvement in sensitivity was found to be 57.4-fold by comparing the slopes of the calibration plot equation of FAAS and SFDF-LPME-FAAS systems. The feasibility of the SFDF-LPME-FAAS method was evaluated by recovery studies using mate tea extracts and tap water samples. The good recovery results obtained for tap water samples and mate tea extracts in the range of 81.1 % - 113.8 % and 85.5 % - 120.8 %, respectively, showed that the method is applicable to similar matrices.
Keywords: Copper; Flame atomic absorption spectrometry; Mate tea; Spray assisted fine droplet formation-liquid; phase microextraction; Tap water; ATOMIC-ABSORPTION-SPECTROMETRY; PRECONCENTRATION; CU; EXTRACTION; COBALT; GREENNESS; CHROMIUM; ELEMENTS; CADMIUM; SOLVENT; Chemistry; Food Science & Technology